Trends in the numbers of Coot Fulica atra and wildfowl Anatidae wintering in France, and their relationship with hunting activity at wetland sites - Fouque, Carol; Guilleman, Matthieu; Schricke, Vincent (Wildfowl, 2009)
Monitoring numbers of wintering wildfowl Anatidae and Coot Fulica atra is an important tool for their management and conservation. Twenty species of wildfowl and Coot have been counted monthly from December–February over 21 winters (1987–2008) at 88 French wetlands of national and international importance for these birds, covering 597 different count sites. Trends in average winter numbers were positive for 15 species, stable for Smew Mergus albellus, and indicated a decline in numbers for the five remaining species. Models assessing trends over time and also the effect of hunting status at the different sites (with sites grouped according to whether the area was hunted, partly hunted, or protected), found that bird numbers varied between sites of different status for all species except Red-crested Pochard Netta rufina. The immediacy with which hunting status affected local trends was less clear. There was no significant interaction between trends in numbers and the hunting status of the count sites for 10 of the 20 Anatidae species, including four of six species protected from hunting. For two protected species, trends were more favourable at fully hunted than at fully protected sites. Ten of the 14 quarry species did not show more favourable trends in protected than in hunted sites. Hunting activity at sites therefore does not, in itself, seem sufficient to explain differences in local trends in waterbird numbers.